Unraveling the impact of greenhouse pepper resistance on biological performance of the broad mite Polyphagotarsonemus latus (Acari: Tarsonemidae) - Elnaz Fadaei; Mohammad Mehrabadi; Abdoolnabi Bagheri; Arash Rashed; Yaghoub Fathipour (Crop Protection, 2024)

Damage caused by Tetranychus urticae and Frankliniella occidentalis on rose plant: effect of different initial population densities - Samaneh Yari; Hamidreza Hajiqanbar; Yaghoub Fathipour; Azadeh Farazmand; Arash Rashed (Arthropod-Plant Interactions, 2024)

Effects of Potato Psyllid Vector Density and Time of Infection on Zebra Chip Disease Development after Harvest and during Storage - Erik J. Wenninger; Nora Olsen; Jeffrey Lojewski; Phillip Wharton; Jennifer Dahan; Arash Rashed; Alexander V. Karasev (American Journal of Potato Research, 2020)
“ Candidatus Liberibacter solanacearum” (Lso) (=“ Candidatus Liberibacter psyllarous”) is an uncultured, phloem-limited bacterium that is associated with zebra chip disease (ZC) in potato ( Solanum tuberosum L.) and transmitted by the potato psyllid ( Bactericera cockerelli (Šulc)). Vector density and timing of infection have been shown to affect ZC prevalence at harvest; however, little work has been done on disease development during storage. Here we confirm with field-cage trials that ZC prevalence at harvest was greater with increased time between inoculation and vine kill. Moreover, we show that with Pacific Northwest growing conditions, ZC can develop over time during storage. Plants inoculated 2 to 3 weeks before vine kill showed little or no ZC symptoms in tubers at harvest, but higher prevalence of symptoms after 3 months in storage. For plants inoculated at 4 to 5 weeks before vine kill, tubers exhibited notable symptoms at harvest, but still showed evidence of symptom development after storage. Plants inoculated within 1 week before vine kill exhibited little or no risk of ZC in tubers at harvest or after storage. Higher vector density tended to contribute to ZC prevalence, but was far less important than timing of infection. These results underscore the potential danger of underestimating ZC prevalence at harvest for tubers being stored long term, and suggest that plants at risk of Lso infection should be protected from potato psyllids until at least 2 weeks before vine kill.

Characterizing Zebra Chip Symptom Severity and Identifying Spectral Signatures Associated with ‘Candidatus Liberibacter solanacearum’-Infected Potato Tubers - Zhiguo Zhao; Sean M. Prager; Regina K. Cruzado; Xi Liang; William R. Cooper; Gongshe Hu; Arash Rashed (American Journal of Potato Research, 2018)

Sugar beet wireworm Limonius californicus damage to wheat and barley: evaluations of plant damage with respect to soil media, seeding depth, and diatomaceous earth application - Arash Rashed; Christopher W. Rogers; Mahnaz Rashidi; Juliet M. Marshall (Arthropod-Plant Interactions, 2017)

Background matching behaviour and pathogen acquisition: plant site preference does not predict the bacterial acquisition efficiency of vectors - Arash Rashed; Nabil Killiny; Joyce Kwan; Rodrigo P. P. Almeida (Arthropod-Plant Interactions, 2011)

The evolution of locomotory behavior in profitable and unprofitable simulated prey - Thomas N. Sherratt; Arash Rashed; Christopher D. Beatty (Oecologia, 2004)